Creative Drama Activities Affecting Primary School Students’ Positive Behavior: กิจกรรมละครสร้างสรรค์ที่มีผลต่อพฤติกรรมเชิงบวกสำหรับนักเรียนชั้นประถมศึกษา - สังขรัตน์ กนิษฐา (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
This research aimed to 1) study the results of Creative Drama activities affecting primary school students’ Positive Behavior at Loisaianusorn school, Bangkok province and 2) study the results of before - after Creative Drama activities affecting primary School students’ Positive Behavior.The sample was 97 primary school students (grade1-3) by Purposive sampling. The results found that the model of creative drama activities using positive behavior theory were respect for dignity, try to participation, considerate motivation, and have a vision, and try to participation accordingly. As each aspect and overall, after creative drama activities had scores higher than before creative drama activities at 0.01 statistically significant level.